Age distribution of Antarctic Bottom Water off Cape Darnley, East Antarctica, estimated using chlorofluorocarbon and sulfur hexafluoride - Ohashi, Yoshihiko; Kawai, Michiyo; 川合, 美千代; カワイ, ミチヨ; Yamamoto, Michiyo; 山本, 美千代; ヤマモト, ミチヨ; Kusahara, Kazuya; Sasaki, Kenichi; Ohshima, Kay I. (Scientific Reports, 2022)
Chlorofluorocarbon (CFC) and sulfur hexafluoride (SF6) were used to investigate the timescale of Antarctic Bottom Water (AABW) that spreads off Cape Darnley (CD) in East Antarctica. The age of the AABW was estimated based on the observed SF6/CFC-12 ratio while taking into account tracer dilution by Lower Circumpolar Deep Water. Along the western canyons off CD and the ~ 3000 to 3500 m isobaths, the bottom water age was < 5 years, reflecting the spread of newly formed CD Bottom Water. Higher ages of ~ 8 years obtained for areas east of CD and > 20 years in the northwestern offshore region indicate inflows of AABW through the Princess Elizabeth Trough and Weddell Sea Deep Water, respectively. This study determined the age distribution in the region off CD, where three different types of AABW spread. journal article